Participatory planning practice in rural Indonesia: A sustainable development goals-based evaluation. Issue 3 (26th May 2020) - Akbar, Aulia; Flacke, Johannes; Martinez, Javier; van Maarseveen, Martin F. A. M.
ABSTRACT: When evaluating the practices of public participation, one should understand how the participatory process is conceived and implemented. Although many studies have been conducted in this regard, there is hardly a study that used Sustainable Development Goals (SDGs) as the basis for evaluation. In this study, we examine the participatory process of a public participation practice in Indonesia, called Musrenbang, at the village level, applying an SDGs' based assessment. Using the case of the Deli Serdang district, we investigate the participatory process based on SDG indicators 11.3.2 and 16.7.2, applying a set of criteria suggested by various scholars. The results show a misalignment between the Musrenbang practice and the evaluation criteria due to key problems such as planning schedules that do not meet regulations, lack of knowledge integration and learning processes, as well as power struggles amongst stakeholders.